Sustainability of Concrete With Synthetic and Recycled Aggregates - Saleh, Hosam M. (IntechOpen, 2022)
Concrete is a material used widely in building and construction applications worldwide; hence, it plays a significant role in the global construction sector. Cement is a major component of concrete and is used in construction applications, either on its own or as a composite with other materials, to improve workability, durability, strength, weight, and shrinkage. However, cement and concrete production and use have adverse environmental effects. Thus, great efforts have been made to produce eco-friendly concrete. This book examines several aspects of sustainable concrete technologies, including new forms of concrete as well as different approaches for creating sustainable cement.